1989
DOI: 10.1161/01.atv.9.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Development of atherosclerosis in genetically hyperlipidemic rabbits during chronic fish-oil ingestion.

Abstract: The evidence for a reduction In cardiovascular mortality from fish oil is based on epidemlologic observations. To test whether fish-oil supplementation Influences the development of atherosclerosis, we treated Watanabe heritable hyperlipidemic rabbits (WHHL), an Inbred strain that spontaneously develops atherosclerosis, with 2.5 ml of MaxEPA flsh-oll concentrate dally and compared them to a control group fed un8upplemented rabbit chow. Serial cholesterol and trlglyceride levels were monitored as were plasma ll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 28 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…The heterozygous WHHL rabbits have the same blood lipid levels as other normolipidaemic rabbits and develop only minimal spontaneous atherosclerosis which is not observed until the age of approximately 2 years (Atkinson et al 1989, Esper et al 1993b, Hansen et al 1994. The WHHL rabbits have been used in dietary and medicamental intervention studies (Rich et al 1989, Chubb et al 1990, Lichtenstein & Chobanian 1990, Mao et al 1991, Hansen et al 1995. The intervention often begins just after the weaning period in 6-week-old rabbits.…”
mentioning
confidence: 99%
“…The heterozygous WHHL rabbits have the same blood lipid levels as other normolipidaemic rabbits and develop only minimal spontaneous atherosclerosis which is not observed until the age of approximately 2 years (Atkinson et al 1989, Esper et al 1993b, Hansen et al 1994. The WHHL rabbits have been used in dietary and medicamental intervention studies (Rich et al 1989, Chubb et al 1990, Lichtenstein & Chobanian 1990, Mao et al 1991, Hansen et al 1995. The intervention often begins just after the weaning period in 6-week-old rabbits.…”
mentioning
confidence: 99%
“…In this respect it is of interest to cite the recent paper by Ravnskov [77] in which he compared the frequency of citation with the outcome of all cholesterol lowering trials using coronary heart disease or death as endpoints and found that positive studies were cited almost six times more often than negative ones. That sample size can be of major importance in determining the out- come of the study was shown by Rich and colleagues [69] who after having analyzed one third of the rabbits, found a statistically significant effect favouring the fish oil treated group. However, because of the variability of aortic atherosclerosis as found in Watanabe hyperlipidemic rabbits it was judged to expand the dietary groups to improve the validity of the results.…”
Section: Fish Oil and The Prevention Of Atherosclerosismentioning
confidence: 90%
“…Animal studies with hypercholesterolemia Tables 2-4 list the in vivo studies in rabbits [58][59][60][61][62][63][64][65][66][67][68][69], swine [23,28,[70][71][72][73] and monkeys [74][75][76], respectively, on the effects of fish oil on the prevention of atherosclerosis and provides details such as the dietary regimen, duration of study, etc. Except in the Watanabe hereditary hyperlipidemic rabbit and one study in pigs [73], all atherogenic diets are highcholesterol diets, and in case of the swine model [28,[70][71][72], bile acids were also needed to enhance hypercholesterolemia.…”
Section: Fish Oil and The Prevention Of Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…In WHHL rabbits, n-3 fatty acids were initially reported to have either no effect on plasma lipids and aortic lesion size (39), or to lower triglycerides, total lipoproteins and cholesterol in female rabbits, but to be ineffective on lesion size of treated vs. untreated controls (40). With a similar experimental protocol, but with different criteria for lesion evaluation, fish oil reduced triglyceride and cholesterol levels and aortic lesions (41).…”
Section: Introductionmentioning
confidence: 99%